Solar radiation energy pulsations in a plant leaf - Sirvydas, Algimantas; Kučinskas, Vidmantas; Kerpauskas, Paulius; Nadzeikienė, Jūratė; Kusta, Albinas (Journal of Environmental Engineering and Landscape Management, 2010)
Solar radiation energy is used by vegetation, which predetermines the existence of biosphere. The plant uses 1–2% of the absorbed radiant energy for photosynthesis. All the remaining share of the absorbed energy, accounting for 99–98%, converts into thermal energy in the plant leaf. At the lowest wind under natural surrounding air conditions, plant leaves change their position with respect to the Sun. An oscillating plant leaf receives a variable amount of solar radiation energy, which causes changes in the balance of plant leaf energies and a changing emission of heat in the leaf. The analysis of solar radiation energy pulsations in the plant leaf shows that when the leaf is in the edge positions of angles 10°, 20° and 30° with respect to the Sun, 1.5%; 6% and 13% less of radiation energy reach the leaf, respectively. During periodic motion, when the amplitude of leaf oscillation is no bigger than 10°, the plant surface receives up to 1.6% less of solar radiation energy within a certain period of time, and when the amplitude of oscillation reaches 30° up to 14% less of solar radiation energy reach the leaf surface. The total amount of radiant energy received during pulsations of solar radiation energy is not dependent on the frequency of oscillation in the same interval of time. Temperature pulsations occur in the leaf due to solar radiation energy pulsations when the plant leaf naturally changes its position with respect to the Sun. Saulės spinduliuotės energijos pulsacijos augalo Santrauka. Saulės spinduliuotės energija būtina augalijai, kuri lemia biosferos egzistavimą. Augalas 1–2 % absorbuotos spinduliuotės energijos sunaudoja fotosintezei, o 99–98 % absorbuotos energijos augalo lape virsta šilumine energija. Natūraliomis aplinkos salygomis esant mažiausiam vėjui augalo lapų padėtis Saulės atžvilgiu keičiasi. Taigi augalo svyruojančio lapo gaunamas Saulės spinduliuotes energijos kiekis yra kintamas, tai sukelia pokyčius augalo lapo energijų balanse ir kintamą šilumos išsiskyrimą lape. Analizuojant Saulės spinduliuotės energijos pulsacijas augalo lape, nustatyta, kad, lapui esant kraštinese 10°, 20° ir 30° kampų padėtyse Saulės atžvilgiu, į jį atitinkamai patenka 1,5 %; 6 % ir 13 % mažiau spinduliuotes energijos. Augalo lapui periodiškai svyruojant, kai svyravimo amplitudė yra iki 10°, per tam tikra laika į lapo paviršių patenka iki 1,6 % mažiau Saules spinduliuotės energijos, o kai svyravimo amplitude siekia iki 30°, – iki 14 % mažiau. Saulės spinduliuotės energijos pulsaciju metu gautas bendras spinduliuotės energijos kiekis nepriklauso nuo to paties laiko intervalo svyravimo dažnio. Dėl Saulės spinduliuotės energijos pulsacijų, natūraliai keičiantis augalo lapo padėčiai Saules atžvilgiu, lape kyla temperatūros pulsacijos. Reikšminiai žodžiai: Saulės energija, energijos srautas, augalo lapas, energijos balansas, pulsacijos, svyravimo dažnis, lapo temperatūra. Пульсации солнечной лучевой энергии в листе растения Резюме. Растения потребляют солнечную лучевую энергию, которая является основой существования биосферы. 1–2% абсорбированной лучевой энергии они используют на фотосинтез. В натуральных условиях при малейшем дуновении ветра листья растений меняют свое положение относительно Солнца. Колеблющийся лист получает переменное количество лучевой энергии, которое вызывает изменения в энергетическом балансе листа растения, что сказывается на переменном выделении тепла в листе. Анализируя пульсации солнечной лучевой энергии в листе растения, установлено, что при крайних положениях листа относительно Солнца на 10, 20 и 30 градусов на лист попадает соответственно на 1,5 %, 6 % и 13 % меньше лучевой энергии. При периодическом колебании листа, когда амплитуда его колебания составляет 10 градусов, за известный промежуток времени солнечная лучевая энергия, попадающая на поверхность листа, уменьшается до 1,6 %, а при амплитуде колебания до 30 градусов соответственно количество лучевой энергии на поверхности листа растения уменьшается до 14%. Установлено, что суммарное количество солнечной лучевой энергии во время пульсации не зависит от частоты колебания листа за одинаковый промежуток времени. Пульсации солнечной лучевой энергии при изменении положения листа растения относительно Солнца вызывают температурные пульсации в листе. Ключевые слова: солнечная энергия, поток энергии, лист растения, энергетический баланс, пульсации, частота колебаний, температура листа. First Publish Online: 10 Feb 2011